Biomimetic Z-scheme photocatalyst with a tandem solid-state electron flow catalyzing H2 evolution. Issue 32 (30th July 2018) - Yu, Weilai; Zhang, Shuai; Chen, Junxiang; Xia, Pengfei; Richter, Matthias H.; Chen, Linfeng; Xu, Wei; Jin, Jingpeng; Chen, Shengli; Peng, Tianyou
Abstract : A biomimetic Z-scheme photocatalyst exhibits dramatically enhanced photocatalytic activity for H2 production, driven by a tandem solid-state electron flow. Abstract : Similar to natural photosynthetic systems, artificial photosynthetic systems require synergistic cooperation between light harvesting, charge separation and redox catalysis. Herein, a three-dimensional (3D) hierarchical photocatalyst is designed with a novel Z-scheme two-photon excitation, defined by the complementary absorption of higher energy and lower energy photons by cadmium sulfide nanowires (CdS NWs) and cobalt–benzimidazole (Co-bIm) coordination polymers (CBPs), respectively. Without any noble-metal co-catalyst, the microscopically integrated CdS–CBP photocatalysts demonstrated dramatically enhanced photocatalytic activities of H2 evolution, which were up to 10.6 folds higher than those of pristine CdS NWs. Structurally, the intimate interfacial contact between the 3D CdS NW scaffold and the discrete CBP microstructures benefits their strong electronic interaction and efficient charge separation. Upon simultaneous light excitation, a tandem solid-state electron flow from CdS to CBP and then from metal (Co) to ligand (bIm) precisely catalyzes the reduction of pre-activated H atoms on the bIm ligands for efficient H2 evolution.